Analytical attributes of Humic Acids derived from tropical-based resources - Balasundram, Siva Kumar; Husin, Aminuddin; Mohd Hanif, Ahmad Husni; Manas, Abdul Rahman (Universiti Putra Malaysia Press, 1998)
Humic acids (HA) are widely researched and exploited compounds due to their exceptional chemical and physical properties. However, information on tropical-based HA is still lacking. This attempted to characterize HA derived from tropical peat and POME using chemical and physical methods. Elemental analysis of the HA showed that C ranged between 48.94 and 57.87%, H between 4.90 and 8.26%, N between 1.93 and 8.05% and 0 between 30.96 and 40.85%. The functional group analysis indicated that peat-derived HA were more reactive than those derived from POME. Optical density and spectral examinations revealed that the HA had varying degrees of aromaticity. Generally, data obtained from the HAs studied (particularly from peat) agreed closely with those reported elsewhere.